Relationship of being threatened or injured with a weapon in school with suicidal ideation and attempt among school students: a school-based study in Zhejiang Province, China - Hao Wang; Huaidong Du; Fiona Bragg; Jieming Zhong; Min Yu (BMC Public Health, 2018)
Abstract Background Suicide is the second leading cause of death among 15–29 year old youths globally, and the third most common external cause of death in China. School bullying can cause serious consequences among adolescents, including psychosocial problems, low self-esteem and post-traumatic stress disorder. Most studies examining the associations between being bullied in school and suicide are from Western, developed countries. Moreover, few studies focus on being threatened or injured with a weapon, which may cause serious body injury. Our study aimed to explore the relationship of being threatened or injured with a weapon in school with suicidal ideation and attempt among middle and high school students in Zhejiang Province, China. Methods A cross-sectional study of 23,543 students in grades 7–12 from 442 schools was carried out through an anonymous self-administered questionnaire between April and May 2017. Multivariable logistic regression models were used to examine the relationship of being threatened or injured with a weapon in school with suicidal ideation and attempt. Results 51.3% of participants were boys, and mean (SD) age was 15.6 (1.7) years. The overall prevalence of suicidal ideation and attempt were 16.1% (95%CI: 15.3–16.9) and 3.6% (95%CI: 3.3–4.0), respectively. Prevalence was higher among girls than boys (ideation: 19.1% vs. 13.3%. attempt: 4.4% vs. 2.9%). 13.2% of students reported being threatened or injured with a weapon in school in the past 12 months (95%CI: 11.9–14.5), higher among boys than girls (15.7% vs. 10.5%), and among rural students than urban students (13.9% vs. 11.6%). After adjustment for socio-demographic status, lifestyle factors, academic performance, self-reported health and mental health, the odds ratios for suicidal ideation and attempt among students who reported being threatened or injured with a weapon were 1.46 (1.31–1.61) and 1.68 (1.31–2.13) respectively, as compared with those who did not report being threatened or injured. Conclusions Preventive measures for physical bullying in school need to be reinforced in China. Being threatened or injured with a weapon is associated with both suicidal ideation and attempt among middle and high school students. Suicide prevention should be an important component of psychological interventions for threatened or injured students.